ANALYSIS OF CONCERN REPORT AND STOP WORK AUTHORITY ON EMPLOYEE OCCUPATIONAL SAFETY AT PT XY - Meldra, Delia Meldra; Yopy Mardiansyah (JURNAL LOGISTICA, 2026)
Occupational health and safety is a crucial aspect in manufacturing industries as it directly affects employee productivity and well-being. PT XY still faces occupational accident risks despite implementing an Occupational Health and Safety Management System. This study aims to analyze the effect of Concern Report Card and Stop Work Authority implementation on employee safety levels. This research uses a descriptive method with a cross-sectional approach. Data were collected through document studies, field observations, and interviews, including work accident data in 2023 and the implementation data of Concern Report and Stop Work in 2024 in the machine shop and weldshop departments. Data analysis was conducted using the Ryan–Joiner normality test and multiple linear regression. The results show that Concern Report and Stop Work significantly affect employee safety improvement with p-values < 0.05. The implementation of both programs successfully reduced workplace accidents and achieved zero accident conditions for eight months in 2024. Therefore, Concern Report and Stop Work are effective tools for improving safety culture in manufacturing industries.